Polio infrastructure strengthened disease outbreak preparedness and response in the WHO African Region. Issue 43 (10th October 2016) - Kouadio, Koffi; Okeibunor, Joseph; Nsubuga, Peter; Mihigo, Richard; Mkanda, Pascal
Highlights: PEI resources are often deployed in response outbreaks of public health emergencies. These PEI contributions to disease outbreaks response have not been documented. The systematic documentation will enhance preparedness for outbreak response. Abstract: Introduction: The continuous deployments of polio resources, infrastructures and systems for responding to other disease outbreaks in many African countries has led to a number of lessons considered as best practice that need to be documented for strengthening preparedness and response activities in future outbreaks. Methods: We reviewed and documented the influence of polio best practices in outbreak preparedness and response in Angola, Nigeria and Ethiopia. Data from relevant programmes of the WHO African Region were also analyzed to demonstrate clearly the relative contributions of PEI resources and infrastructure to effective disease outbreak preparedness and response. Results: Polio resources including, human, financial, and logistic, tool and strategies have tremendously contributed to responding to diseases outbreaks across the African region. In Angola, Nigeria and Ethiopia, many disease epidemics including Marburg Hemorrhagic fever, Dengue fever, Ebola Virus Diseases (EVD), Measles, Anthrax and Shigella have been controlled using existing polio Eradication Initiatives resources. Polio staffs are usually deployed in occasions to supports outbreak response activities (coordination, surveillance, contact tracing, case investigation, finance, data management, etc.). Polio logistics such vehicles, laboratories were also used in the response activities to other infectious diseases. Many polio tools including micro planning, dashboard, guidelines, SOPs on preparedness and response have also benefited to other epidemic-prone diseases. The Countries' preparedness and response plan to WPV importation as well as the Polio Emergency Operation Center models were successfully used to develop, strengthen and respond to many other diseases outbreak with the implication of partners and the strong leadership and ownership of governments. This review has important implications for WHO/AFRO initiative to strengthening and improving disease outbreak preparedness and responses in the African Region in respect to the international health regulations core capacities.